MicroRNA profiling of primary high-grade soft tissue sarcomas - Renner, Marcus; Penzel, Roland; Eils, Roland; Schirmacher, Peter; Mechtersheimer, Gunhild (Genes, chromosomes & cancer, 2012)
High-grade soft tissue sarcomas are a heterogeneous and complex group of tumors. MicroRNAs (miRNAs) are considered as attractive candidates that may improve diagnostic, prognostic, and predictive characterization of this group of malignancies. We performed a comprehensive miRNA expression analysis in a series of 76 untreated, primary high-grade soft tissue sarcomas representing eight subtypes, and in a panel of 15 representative sarcoma cell lines using microarray technology. This screening revealed unique miRNA expression patterns for synovial sarcomas, myxoid liposarcomas, and leiomyosarcomas, and defined unique sets of miRNAs discriminating the different liposarcoma subtypes from non-neoplastic adipose tissue. The over-represented miRNAs included members of the miR-200 family in synovial sarcomas, and the tumor-associated miR-9 and miR-9* in myxoid liposarcomas compared to adipose tissue. Moreover, we found coexpression of 63 miRNAs clustering in a genetically imprinted chromosomal region 14q32.2 separating primary sarcoma samples and sarcoma cell lines into two molecular subgroups. Taken together, our comprehensive miRNA profiling identified a novel set of miRNAs that might contribute to sarcomagenesis and provide a starting point for experimental modulation of relevant targets for new therapeutic strategies in high-grade sarcomas. © 2012 Wiley Periodicals, Inc.